Comparison of Electronic Structure and Magnetic Properties of Few Layer Graphene and Multiwall Carbon Nanotubes - Sekhar Chandra Ray (Advances in Materials Science and Engineering)
A comparative study has been made for the non-catalyst based few layer graphene (FLG) and Fe-catalyst based multiwall carbon nanotubes (MWCNTs). Magnetic and electronic properties of FLG and MWCNTs were studied using magnetic M-H hysteresis loops and synchrotron radiation based X-ray absorption fine structure spectroscopy measurements. Structural defects and electronic and bonding properties of FLG/MWCNTs have been studied using Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and ultraviolet photoelectron spectroscopy (UPS). The work functions of FLG and MWCNTs are 4.01 eV and 3.79 eV, respectively, obtained from UPS (He-I) spectra. UPS (He-II) results suggest that the density of states (DOS) of MWCNTs is higher than FLG and is consistent with Raman spectroscopy result that shows the defect of MWCNTs is higher than FLG. The magnetic coercivity (Hc) of the MWCNTs (~750 Oe) is higher than FLG (~85 Oe) which could be used for various technological magnetic applications.